Predictors of career success: a study among academic staff in northern region, Malaysia / Siti Meriam Ali, Mohd Rizaimy Shaharudin, Azyyati Anuar - Ali, Siti Meriam; Shaharudin, Mohd Rizaimy; Anuar, Azyyati (Institute of Research Management & Innovation (IRMI), 2013)
The purpose of this study is to determine the predictors of career success among Malaysia academicians. Specifically, this study investigates the relationship between human capital factors (job position and work experience), organizational sponsorship factors (perceived organizational support and perceived supervisory support), personality (self-efficacy), career commitment and career success. The sample of this study consisted of 100 academic staff of one particular institution of higher learning in the Northern region of Malaysia. Firstly, the human capital (job position and work experience) has positive significant relationship with the objective career success. However, there is an insignificant relationship that exists between the human capital and the subjective career success. Secondly, organizational sponsorship (perceived organizational support and supervisory support) has insignificant relationship with the objective career success. However, there is a partial relationship that exists between the organizational sponsorship with the subjective career success, on which perceived organizational support has a significant relationship with the subjective career success but not to the factor of supervisory support. Thirdly, personality supports a full relationship with the objective and subjective career success. Finally, career commitment has no relationship with the career success since no significant effect was found exists with both, objective and subjective career success. Examination of the relative importance of each independent variable on subjective career success (career satisfaction) revealed that perceived organizational support and self-efficacy were most important in explaining career satisfaction. Other factors such as job position, work experience, supervisory support and career commitment were not significant to influence the employee’s career satisfaction. Except for career commitment, the rest of study variables showed mixed result. To the surprised, career commitment was found to be insignificant effect to both objective and subjective career success. Another variable, human capital (job position and work experience) were found to be positive significant related to objective career success (number of promotion) but not to the subjective career success (career satisfaction). A different way has been demonstrated by the variable of self-efficacy which was found to have positive significant effect on the subjective career success, but not to the objective career success. However, both dimensions of organizational sponsorship (perceived organizational support and supervisory support) as insignificant relationship with the career success, although they partially influenced the subjective career success but realized full insignificant effects towards the objective career success. Future research should be conducted to determine if the results could be replicated empirically through more diverse and larger sample of the study. In addition, since the result of this research is connected well with some of the earlier publications regarding career success, further research in this area is expected to contribute to the existing body of knowledge, particularly on the use of new variables and analysis using robust analysis software such as Structural Equation Modeling. As mentioned, it would be useful to complement this research with the studies from other perspectives other than the academic staff, so that the generalization of the results towards the practicality and theory enrichment in the area can be successfully reached.